Interaction of the gastroenterologist and psychiatrist at management of patient with functional disorder of gastro-intestinal tract - V. T. Ivashkin; Ye. A. Poluektova; A. G. Beniashvili (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of publication. To present clinical case of the patient with functional disorder of gastro-intestinal tract (GIT) at combined management by gastroenterologist and psychiatrist.Original positions. Patient Ch was monitored in the V.Kh.Vasilenko Clinic of propedeutics of internal diseases, gastroenterology and hepatology since 2001. Taking into account patient’s complaints (bloating and abdominal pain relieved after defecation, frequent stool up to 3–5 times per day, incidental imperative urgency to defecation and feeling of incomplete defecation), and long-term benign course of disease, absence of organic changes, according to results of laboratory tests and instrumental investigations irritable bowel syndrome has been diagnosed. However with the account of indications for psychiatrist consultation of patients of the functional diseases of GIT patient was referred to psychiatrist, first, for disorder of social adaptation which could not be explained by presence of GIT-related complaints, and second, each dialogue with him invoked inexplicable negative reaction in nurses and doctors. Patient received course of symptomatic treatment on which background some improvement of intestinal complaints was achieved. At the end of treatment patient was consulted by psychiatrist according to which opinion the state of the patient conformed several ICD10 headings, first of all to the mixed anxiety-depressive disorder, as well as to somatoform disorder of autonomous dysfunction type. Antianxiety treatment has been prescribed at which anxiety improved slightly. From now on the patient was constantly monitored by gastroenterologist and psychiatrist that allowed to improve considerably his social adaptation and to reduce severity of somatic complaints.Conclusion. This case reflects problem of major group of patients, whose somatic complaints cannot be more exhaustively explained at objective medical investigation. Till now still there is no established position on treatment of such patients, significant part of whom receives treatment recommended at clinically similar somatic disease. In some cases their treatment can be not only conservative, but also invasive: operations, repeated diagnostic manipulations, etc. In some cases, when the physician implicates mental parentage of somatic symptoms, certain patients are referred to psychiatrist. More and more doctors recognize pathogenic relation between psychological disorders and physical symptoms without obvious organic substrate and, therefore — necessity of creation of interdisciplinary alliances to provide qualified aid to considerable number of such patients.